Poverty alleviation in the light of Quran and Sunnah: a maqassid approach - Zakariyah, Habeebullah; Maikabara, Abdullateef Abdulqadir (2019)
Poverty is considered as a multifaceted concept that can be in several forms which typically symbolize lack of the necessary means to meet human personal needs such as food, shelter and clothing. People witness poverty in various ways as part of the nations’ population is living in an average poverty status while others are in an extremely poverty mostly in the rural areas. However, the evolution of poverty has been an emerging economic phenomena and focus of national and international government in Muslim and non-Muslim countries to initiate various strategies and programs for the poverty alleviation. In Islam, it is imperative to cater for the betterment of the society and well-being of the people leaving under the same roof of the system. This paper attempts to analyze poverty alleviation approaches from Quran and Sunnah perspective. For this purpose, inductive research method to articulate the approaches in the light of Quran and Sunnah, which are explicitly and implicitly encompass all the aspects of life. This will revive Muslims’ mindset to refer back to guidelines and teachings of Islam for a perfect way to tackle any possible calamity that will or might endanger the stability and sustainability of Muslim affairs. It was articulated that poverty can be alleviated through corporation, brotherhood assistance, fairness and equality, and engagement in business.